2015
DOI: 10.1007/s11214-015-0187-2
|View full text |Cite
|
Sign up to set email alerts
|

The Earth: Plasma Sources, Losses, and Transport Processes

Abstract: This paper reviews the state of knowledge concerning the source of magnetospheric plasma at Earth. Source of plasma, its acceleration and transport throughout the system, its consequences on system dynamics, and its loss are all discussed. Both observational and modeling advances since the last time this subject was covered in detail (Hultqvist et al., Magnetospheric Plasma Sources and Losses, 1999) are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 331 publications
(358 reference statements)
0
69
0
Order By: Relevance
“…Although the model reproduces the density trend observed by Polar, the radial position of this transition does not match precisely, and there are several reasons why this behavior is expected. First, while ionospheric outflow is driven by many processes, both kinetic and fluid [see, e.g., Welling et al , , and references therein], only a handful of outflow processes are captured in MHD without including a stand‐alone outflow model [ Welling and Liemohn , ]. This is especially true in the cusp.…”
Section: Magnetohydrodynamicsmentioning
confidence: 99%
“…Although the model reproduces the density trend observed by Polar, the radial position of this transition does not match precisely, and there are several reasons why this behavior is expected. First, while ionospheric outflow is driven by many processes, both kinetic and fluid [see, e.g., Welling et al , , and references therein], only a handful of outflow processes are captured in MHD without including a stand‐alone outflow model [ Welling and Liemohn , ]. This is especially true in the cusp.…”
Section: Magnetohydrodynamicsmentioning
confidence: 99%
“…Finally, the ionospheric outflow of ions (Welling et al 2015) is very important. The ionosphere (the ionized upper atmosphere) is a huge reservoir of cold ions that are gravitationally bound to the Earth.…”
Section: Important Physical Processesmentioning
confidence: 99%
“…The ionospheric outflow of ions (Welling et al 2015), particularly O + , increases as the driving of the magnetosphere by the solar wind increases. Ionospheric outflow has different properties coming from different regions of the Earth: e.g., the polar caps, the sunlit dayside, the nightside auroral zone.…”
Section: Types Of Activity In the Magnetospheric Systemmentioning
confidence: 99%
“…Following this new found excitement of outflow was the identification of another potential feedback loop [ Welling et al , ]. Using the first‐principle‐based PWOM model with global MHD and a dedicated ring current model, it was found that region 2 Birkeland currents could increase the amount of outflowing O + via a previously known mechanism [ Gombosi and Nagy , ].…”
Section: Mass‐energy Feedbackmentioning
confidence: 99%
“…Hydrogen, oxygen, and total fluence (orange, green, and black lines, respectively) taken at the interface between the PWOM and BATS‐R‐US during the one‐way coupled simulation (solid lines) and the two‐way coupled simulation (dashed lines). Reproduced from Welling et al [].…”
Section: Mass‐energy Feedbackmentioning
confidence: 99%